2014
DOI: 10.1371/journal.pone.0098296
|View full text |Cite|
|
Sign up to set email alerts
|

Individual Differences in Ethanol Locomotor Sensitization Are Associated with Dopamine D1 Receptor Intra-Cellular Signaling of DARPP-32 in the Nucleus Accumbens

Abstract: In mice there are clear individual differences in the development of behavioral sensitization to ethanol, a progressive potentiation of its psychomotor stimulant effect. Variability in the behavioral responses to ethanol has been associated with alcohol preference. Here we investigated if the functional hyperresponsiveness of D1 receptors observed in ethanol sensitized mice leads to an increased activation of DARPP-32, a central regulatory protein in medium spiny neurons, in the nucleus accumbens - a brain reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 33 publications
(42 reference statements)
0
9
0
Order By: Relevance
“…Thus, it would have been expected that an increase in DA levels induced by EtOH would lead to an increase in pDARPP‐32‐Thr75 in D 2 containing neurons. Consistent with models of striatal function and DA‐related signal transduction, EtOH (1.5 g/kg) in rats has shown to increase phosphorylation of DARPP‐32 at Thr34 in striatum (Nuutinen et al, 2011), and EtOH ‐sensitized mice have shown functional hyperresponsiveness of D 1 receptors in Acb, which induced higher pDARPP‐32(Thr34) in sensitized mice (Abrahao et al, 2014). However, in our study, pDARPP‐32(Thr75) was not affected by EtOH or by the EtOH plus caffeine combination.…”
Section: Discussionmentioning
confidence: 79%
“…Thus, it would have been expected that an increase in DA levels induced by EtOH would lead to an increase in pDARPP‐32‐Thr75 in D 2 containing neurons. Consistent with models of striatal function and DA‐related signal transduction, EtOH (1.5 g/kg) in rats has shown to increase phosphorylation of DARPP‐32 at Thr34 in striatum (Nuutinen et al, 2011), and EtOH ‐sensitized mice have shown functional hyperresponsiveness of D 1 receptors in Acb, which induced higher pDARPP‐32(Thr34) in sensitized mice (Abrahao et al, 2014). However, in our study, pDARPP‐32(Thr75) was not affected by EtOH or by the EtOH plus caffeine combination.…”
Section: Discussionmentioning
confidence: 79%
“…The protein analysis data show that ethanol exposure mimics exposure to a D1-like agonist in mice lacking D2Rs on medium spiny neurons. Previous work suggests a positive correlation between ethanol-induced stimulation and the sensitivity of D1Rs in the striatal pathway (Abrahao et al, 2014). We speculated that the D1R hypersensitivity in iMSN-Drd2KO mice could be the underlying mechanism driving the enhanced ethanol stimulation and ethanol preference.…”
Section: Resultsmentioning
confidence: 90%
“…Nicotine regulates multiple DARPP-32 phosphorylation sites in striatal slices as well as in vivo after nicotine abstinence (Hamada et al, 2004(Hamada et al, , 2005Abdolahi et al, 2010). These studies did not show alterations in total DARPP-32 protein levels, although other drug treatments such as alcohol, methylphenidate, and cocaine can regulate total DARPP-32 protein levels (Lynch et al, 2007;Souza et al, 2009;Abrahao et al, 2014). In the current study DARPP-32 was significantly increased in the VTA of MC vs. FC mice in both mouse strains, and in the NAc of MC vs. FC C3H/HeJ mice.…”
Section: Individual Proteinsmentioning
confidence: 79%